Artificial intelligence or human decision-making: A case study on crisis response following an earthquake - Milić, Igor; Bilić, Krunoslav; Janeš, Hrvoje (Crisis Management Days, 2025)
Decision-making in crisis situations, such as earthquakes, requires rapid information gathering and analysis, as well as the optimal allocation of resources. Traditionally, humans have been responsible for making key decisions in such scenarios. However, with advancements in artificial intelligence (AI), the question arises as to whether AI can surpass human decision-making capabilities in crisis situations. This case study examines the advantages and limitations of decision-making by both AI and humans in crisis management following devastating earthquakes. AI systems leverage vast real-time data, including demographic and spatial information, planning documents such as risk assessments and emergency response plans, as well as analyses of past disasters, to generate rapid decision-making recommendations for mitigating consequences of earthquakes. In contrast, crisis managers rely on experience, intuition, and ethical judgment, which are often indispensable in highly unpredictable scenarios. Empirical research indicates that the integration of AI-driven analytics with human expertise yields the most effective outcomes—AI facilitates the rapid identification of patterns and recommends response measures, while human decision-makers provide the final assessment, ensuring the incorporation of critical social and ethical considerations. This study concludes that artificial intelligence can significantly enhance decision-making in crisis situations following earthquakes; however, human expertise remains essential for contextual adaptation to the specific characteristics of each crisis. It is recommended that AI-driven decision support systems be further developed in close collaboration with crisis management experts to ensure their effective and ethical implementation.